Pengaruh Literasi Keuangan dan Spending Self-Control Terhadap Gaya Hidup Generasi Z di Daerah Khusus Jakarta - Ramanda, Rico (LANCAH: Jurnal Inovasi dan Tren, 2024)
In its development, the consumptive lifestyle of buying what they want rather than what they need has become a common habit for Generation Z. This is because they spend more than they earn, potentially leading to financial problems in the future. This can be seen from the fact that the expenses incurred are more than the income of each individual, potentially causing financial problems in the future. However, this can be minimized by the existence of Financial Literacy and spending self-control that can improve the financial understanding of Generation Z in general. This study aims to determine the effect of Financial Literacy and spending self-control on Lifestyle. The subjects of this study amounted to 100 Generation Z respondents in the Special Region of Jakarta using purposive sampling technique using the cochran formula. The results stated that the Financial Literacy variable has a positive and significant influence on Lifestyle, the spending self-control variable has a positive and significant influence on Lifestyle, and the Financial Literacy and spending self-control variables together have a positive and significant influence on Lifestyle.